(untitled) (Asian Journal of Ethnobiology, 2025)
Abstract. Hafizah N, Chikmawati T, Djuita NR, Purwanto Y. 2025. Ethnobotany and traditional food plant knowledge among the Malay community of Kuantan Singingi District, Riau, Indonesia. Asian J Ethnobiol 8: 271-290. The Malay community in Kuantan Singingi District, Riau Province, Indonesia, is known for its unique culture and cuisine. However, their local knowledge and wisdom regarding the use of food plants have not been documented. This study aims to change that, documenting and analyzing diversity, identifying the local importance of species, and supporting sustainable biodiversity conservation. The research was conducted across five villages in Kuantan Singingi District, using open-ended, semi-structured, and structured interviews with 107 informants selected through purposive and snowball sampling methods. Data were analyzed to show Use Value (UV), Relative Frequency of Citation (RFC), Index of Cultural Significance (ICS), and Important Value Index (IVI). A total of 167 plant species belonging to 55 families were recorded, dominated by Fabaceae (13 species). Trees (40.12%) and herbs (33.53%) were the most common growth forms, with fruits (44.74%) and leaves (22.11%) as the main parts used. Cocos nucifera exhibited the highest UV, RFC, and ICS, reflecting its central cultural and culinary role. Knowledge was found to be influenced by gender, age, and occupation, with women and older generations serving as primary custodians. This study provides the first comprehensive documentation of food plant knowledge in Kuantan Singingi. It underscores the need for conservation strategies, intergenerational knowledge transfer, and integration of ethnobotanical knowledge into education to sustain both biodiversity and cultural heritage.